Decoding CKD-induced muscle atrophy through the critical role of lncRNA GAS5 and pyroptosis - Rong Huang; Xinying Tang; Shuang Liu; Lijing Sun (Molecular Therapy: Nucleic Acids)
Skeletal muscle atrophy is a prevalent complication of chronic kidney disease (CKD) and serves as an indicator of adverse prognosis and poor quality of life; however, the underlying mechanisms remain ambiguous. Emerging evidence has shown that long non-coding RNAs (lncRNAs) are involved in the pathogenesis of skeletal muscle atrophy. Using RNA sequencing (RNA-seq), we discerned elevated GAS5 expression in the muscles of CKD mice and verified these findings by real-time qPCR. Transmission electron microscopy confirmed morphological signs of pyroptosis, a potentially causal cellular death form. Additionally, elevated levels of pyroptosis markers, such as NLRP3, cleaved caspase-1, and GSDMD-N, were observed in CKD mouse models and lipopolysaccharide (LPS)/ATP-stimulated C2C12 myotubes. Intriguingly, the knockdown of GAS5 reduced these markers, alleviating pyroptosis and enhancing myofiber size, both in vitro and in vivo. Furthermore, we pinpointed an interaction between GAS5 and the mitochondrial translation elongation factor (TUFM) through RNA pull-down and mass spectrometry. This interaction amplified NLRP3 activity, contributing to pyroptosis and muscle atrophy. Notably, overexpressing TUFM counterbalanced this effect. Fundamentally, the interaction between GAS5 and TUFM appears to compromise the anti-pyroptosis capacity of TUFM. Consequently, this amplifies the activation of the NLRP3 pathway, which may underpin the crucial mechanism driving pyroptosis-mediated muscle atrophy. Our findings provide new evidence for GAS5’s role in regulating cellular pyroptosis in CKD-induced skeletal muscle atrophy.